2015
DOI: 10.1074/jbc.m115.636795
|View full text |Cite
|
Sign up to set email alerts
|

TGFβ-activated Kinase 1 (TAK1) Inhibition by 5Z-7-Oxozeaenol Attenuates Early Brain Injury after Experimental Subarachnoid Hemorrhage

Abstract: Background: Role of TGF␤-activated kinase 1 (TAK1) in the pathogenesis of early brain injury after subarachnoid hemorrhage (SAH) has not been reported. Results: TAK1 inhibition attenuates early brain injury and improves neurological deficits after SAH. Conclusion: TAK1 inhibition exhibits neuro-protective effects possibly through anti-apoptotic function. Significance: These results provide a novel target for SAH treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 46 publications
(45 reference statements)
2
45
0
Order By: Relevance
“…In line with the data from a previous study, the level of total TAK1 kept constant after SAH and p-TAK1 increased significantly after SAH, indicating that TAK1 was activated post SAH (Fig. 3a ) 34 . While ST2825 treatment significantly reduced the levels of p-TAK1.…”
Section: Resultssupporting
confidence: 91%
“…In line with the data from a previous study, the level of total TAK1 kept constant after SAH and p-TAK1 increased significantly after SAH, indicating that TAK1 was activated post SAH (Fig. 3a ) 34 . While ST2825 treatment significantly reduced the levels of p-TAK1.…”
Section: Resultssupporting
confidence: 91%
“…Together with the role TAK1 plays in the MAPK pathway, it is also well documented as important in mediating NF‐κB activity in various cell types including HeLa, HEK293T, ex vivo neurons, microglia cells, and B and T lymphocytes, to name a few 24 , 45 48–52 ; however, the precise nature of the TAK1 role has been a challenge to dissect at times. In B cell receptor (BCR) signaling, based on differential knockout models, the kinase activity of TAK1 was shown to be dispensable on the one hand, 45 while others later demonstrated that the physical protein, likely via its interactions 53 (e.g., TAB2 and TAB3) were critical 52 .…”
Section: Discussionmentioning
confidence: 99%
“…It was phosphorylated in satellite cells upon skeletal muscle injury induced by barium chloride and promoted myofiber regeneration . TAK‐1 was also activated in brain injury following experimental subarachnoid hemorrhage or trauma, and its inhibition reduced downstream signaling and neurologic deficits .…”
Section: Discussionmentioning
confidence: 99%